Solve 4(x - 3) - 2(x - 1) > 0.
1 answer:
Answer:
![x>5](https://tex.z-dn.net/?f=x%3E5)
Step-by-step explanation:
<u><em>Step 1: Simplify both sides of the inequality:</em></u>
→ ![2x-10>0](https://tex.z-dn.net/?f=2x-10%3E0)
<u><em>Step 2: Add 10 to both sides:</em></u>
→ ![2x-10+10>0+10](https://tex.z-dn.net/?f=2x-10%2B10%3E0%2B10)
![2x>10](https://tex.z-dn.net/?f=2x%3E10)
<u><em /></u>
<u><em>Step 3: Divide both sides by 2:</em></u>
→ ![\frac{2x}{2}> \frac{10}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%7D%7B2%7D%3E%20%5Cfrac%7B10%7D%7B2%7D)
![x>5](https://tex.z-dn.net/?f=x%3E5)
You might be interested in
Answer:
1
Step-by-step explanation:
move up one and over one, 1/1 = 1
Use your keyboard and if that doesn’t work on the right top comet there’s a pen that should work :))
Answer:
2 ≤ x < 7
Step-by-step explanation:
-1 ≤ x – 3 < 4
Add 3 to each side
-1+3 ≤ x – 3+3 < 4+3
2 ≤ x < 7
Answer:
area formula: base x height 9x4=36
Step-by-step explanation:
Answer:13 miles
Step-by-step explanation:10.20-1.75=8.45÷0.65=13